The effect of a low volume pharmaconutrition supplement with antioxidants and glutamine (Intestamine®) administration to critically ill patients on the prevalence of infection, ventilation requirements and duration of intensive care unit stay : a pilot study - Van Niekerk, Hester Susanna (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2010.